In situ elemental, Sr isotope composition of plagioclase and elemental composition of clinopyroxene and thermobarometric data of andesite from Kueishantao, north of Taiwan, China - Guo, Kun; Wang, Xiaoyuan; Chen, Shuai (PANGAEA, 2021)
This dataset reports in situ major and trace elements, Sr isotopic ratios of plagioclase and in situ major and trace elements of clinopyroxene of andesite from Kueishantao, north of Taiwan, China. The andesite belongs to the subalkaline, tholeiitic and calc-alkaline magma series. The phenocryst minerals in andesites from KST account for 80-90% of the whole-rock samples, including plagioclase, cinlopyroxene, orthopyroxene, Fe-Ti oxides, zircon and apatite. Major element compositions of Pl and Cpx were obtained with a JEOL JXA-8230 electron microprobe at Ocean University of China. Trace element compositions were obtained with LA-ICP-MS at the Wuhan Sample Solution Analytical Technology Co., Ltd. Sr isotope ratios of Pl were measured by a Neptune Plus MC-ICP-MS (Thermo Fisher Scientific, Bremen, Germany) in combination with a GeoLas HD excimer ArF laser ablation system (Coherent, Göttingen, Germany) at the Wuhan Sample Solution Analytical Technology Co., Ltd. Considering all geochemical, 87Sr/86Sr isotope and geophysical constraints, the principal magma source of KST andesites was probably the lower continental crust, which foundered into the convecting mantle and subsequently melted and interacted with asthenospheric mantle materials. A full discussion of the results can be found in the related article.
Keywords: andesite; clinopyroxene; in-situ mineral geochemistry; in-situ Sr isotope; plagioclase